Equivalence in translation: balancing act between source and target cultures in Dream of the Red Chamber - Tian, Dandan; Abdullah, Muhammad Alif Redzuan; Wong, Ling Yann (Bilingual Publishing Group, 2022)
This study explores the intricate balance between source and target cultures in the translation of the classic Chinese novel, “Dream of the Red Chamber,” focusing on the concept of equivalence in translation. By examining two distinct yet far-reaching translations of this seminal work by David Hawkes and Yang Xianyi and Gladys Yang, this paper highlights the challenges and strategies translators employ to navigate cultural nuances, idiomatic expressions, and historical contexts unique to the original text. The research methodology includes a comparative analysis of selected passages from the original text and their counterparts in multiple English translations, assessing how different translators have approached key cultural and linguistic elements. Findings reveal that achieving equivalence in translation extends beyond literal word-for-word translation; it encompasses a deeper understanding and interpretation of the source culture’s socio-cultural and historical intricacies. The study also discusses the implications of these translation choices for readers’ appreciation and understanding of the novel’s themes and cultural depth. This paper contributes to the field of future translation studies by offering insights into the dynamic interplay between fidelity to the source text and the adaptability required to resonate with target culture readers, thereby enriching the discourse on cultural preservation and adaptation in literary translation. Copyright © 2024 by the author(s).